A single scalp nodule as the first presentation of acute lymphoblastic leukemia (KMT2A::MLLT3) in a healthy-appearing infant: a case report - Pellegrino, Francesco; Coppo, Paola; Barisone, Elena; Bertorello, Nicoletta; Spadea, Manuela; Fagioli, Franca (Frontiers in Pediatrics, 2023)
Backgroud Infant leukemia is a rare form of acute leukemia diagnosed prior to 1 year of age with an extremely poor prognosis, due to its dismal response to current therapies. It comprises about 4% of childhood acute lymphoblastic leukemia (ALL). Isolated initial cutaneous involvement in ALL is very uncommon, and even more in infant ALL. Case Presentation Here we present a case of 2-month-old healthy - appearing infant, presenting with a single scalp nodule and subsequently diagnosed with an infant ALL. It was characterized by the most immature B-lineage immunophenotype (pro-B ALL/B-I according to European Group for the Immunological Characterization of Leukaemias - EGIL - classification) and chromosomal translocation t(9;11)(p22;q23) resulting in the fusion gene KMTLA2::MLLT3, that is a negative prognostic factor. She underwent hematopoietic stem cell transplantation (HSCT) and she is still in remission. Conclusions This represents a peculiar case because isolated initial cutaneous involvement in ALL is rare. Although the healthy-appearing patients, every suspicious symptom for malignancies should be further investigated to anticipate the diagnosis and start treatment early.